Loneliness, self‐esteem, and life satisfaction as predictors of Internet addiction: A cross‐sectional study among Turkish university students. Issue 4 (12th April 2013) - Bozoglan, Bahadir; Demirer, Veysel; Sahin, Ismail
<x xml:space="preserve">Abstract</x> This study investigated the relationship among loneliness, self‐esteem, life satisfaction, and Internet addiction. Participants were 384 university students (114 males, 270 females) from 18 to 24 years old from the faculty of education in Turkey. The Internet Addiction, UCLA Loneliness, Self‐esteem, and Life Satisfaction scales were distributed to about 1000 university students, and 38.4% completed the survey (see Appendix A and B). It was found that loneliness, self‐esteem, and life satisfaction explained 38% of the total variance in Internet addiction. Loneliness was the most important variable associated with Internet addiction and its subscales. Loneliness and self‐esteem together explained time‐management problems and interpersonal and health problems while loneliness, self‐esteem, and life satisfaction together explained only the interpersonal and health problems subscales.